2015
DOI: 10.1186/s40781-015-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

GAPDH, β-actin and β2-microglobulin, as three common reference genes, are not reliable for gene expression studies in equine adipose- and marrow-derived mesenchymal stem cells

Abstract: BackgroundQuantitative real time reverse transcription PCR (qRT-PCR) is one of the most important techniques for gene-expression analysis in molecular based studies. Selecting a proper internal control gene for normalizing data is a crucial step in gene expression analysis via this method. The expression levels of reference genes should be remained constant among cells in different tissues. However, it seems that the location of cells in different tissues might influence their expression. The purpose of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 44 publications
3
18
2
Order By: Relevance
“…Total protein was harvested from cultured cells with ice-chilled radioimmunoprecipitation assay lysis buffer (ThermoFisher Scientific There are several limitations we have to acknowledge. In 2015, Nazari et al reported that GAPDH and β-actin were not appropriate for normalization of mRNA in adipocytes or adipose tissue (20). We conducted some experiments using both β-actin and tubulin as reference genes, and the results are consistent with previous data in which tubulin was used as the reference gene.…”
Section: Immunoblot Analysissupporting
confidence: 87%
“…Total protein was harvested from cultured cells with ice-chilled radioimmunoprecipitation assay lysis buffer (ThermoFisher Scientific There are several limitations we have to acknowledge. In 2015, Nazari et al reported that GAPDH and β-actin were not appropriate for normalization of mRNA in adipocytes or adipose tissue (20). We conducted some experiments using both β-actin and tubulin as reference genes, and the results are consistent with previous data in which tubulin was used as the reference gene.…”
Section: Immunoblot Analysissupporting
confidence: 87%
“…Medrano found that GAPDH was one of the best genes in combination for embryonic samples (Medrano et al, 2017 ). Our results were consistent with these previous studies suggesting that GAPDH can also be universally used as a reference gene in radish and their relatives, although several reports in animal and plant systems have suggested that GAPDH has some limitations as an internal control gene (Sirover, 1999 ; Nazari et al, 2015 ). The reference gene UP2 , encoding an uncharacterized conserved protein, is related to cell structure.…”
Section: Discussionsupporting
confidence: 93%
“…It is generally known that GAPDH and β-actin are the two most commonly-used reference genes. However, some researchers have identified that GAPDH and β-actin showed a significant variation in different cells, tissues and experimental conditions [24,25,26]. Furthermore, Catalan and his colleagues showed that GAPDH is a less appropriate reference gene in human omental and subcutaneous adipose tissue from obesity and type 2 diabetes patients, because of the variational expression [27].…”
Section: Discussionmentioning
confidence: 99%